Integrating Information and Communication Technology (ICT) into university teaching and learning: a case study / Chan Yuen Fook and Gurnam Kaur Sidhu - Chan, Yuen Fook (ACRULeT, Faculty of Education & UiTM Press, 2009)
Over the past decade the push for academics to develop competencies in the use of information and communication technologies (ICT) in teaching and learning has increased. Within the Malaysian context unfortunately, until now there has not been a holistic and conclusive study on the integration of ICT in higher education. This exploratory study examined the integration of ICT among academics for the enhancement of university teaching and learning. A descriptivecorrelational research methodology that employed a survey questionnaire was used in this case study. The data was analyzed using means, standard deviation, t-test, ANOVA, and correlation. The findings indicated that the ICT facilities in the higher instituion left much to be desired and the usage of ICT in teaching among the academics was not at a satisfactory level. Even though a majority of the acdemics are aware of the many benefits of ICT there still exists academics who hold firm to the importance of face-to-face interaction and the didactic role of the instructors. The findings also revealed that the integration of ICT into the classroom focuses mainly on teaching and learning rather than the technical knowhow about computers themselves and how this technology helps support users to participate in the integration of ICT into teaching and learning. However, most of the respondents have shown a keen willingness to adopt ICT in their future teaching and learning processes once proper training and relevant technical support are provided. The findings, in general, can help lecturers, IT staff and university management to manage the integration of ICT in university teaching and learning in a more organized manner. The findings also would enable the faculty to be more responsive to the needs of staff and students to effectively address the critical problems related to the integration of technology into university teaching and learning in ways that are both contextualized and authentic.